2000
DOI: 10.1093/oxfordjournals.bja.a013380
|View full text |Cite
|
Sign up to set email alerts
|

Rocuronium potency and recovery characteristics during steady-state desflurane, sevoflurane, isoflurane or propofol anaesthesia

Abstract: We have studied the potency and recovery characteristics of rocuronium during 1.25 MAC of isoflurane, desflurane, sevoflurane or propofol anaesthesia in 84 patients using electromyography. Potency was determined by a cumulative bolus technique. The mean ED50 of rocuronium was 169 (SD 41), 126 (32), 121 (28) and 136 (25) micrograms kg-1 during propofol, isoflurane, sevoflurane and desflurane anaesthesia, respectively (ns), and ED90 values were 358 (62), 288 (29), 289 (28) and 250 (28) micrograms kg-1, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 14 publications
7
58
1
Order By: Relevance
“…[14][15][16] This may be the reason why in a recent study there was no marked prolongation in average reversal time of rapacuronium during sevoflurane compared to propofol anesthesia as the reversal was carried out within only about 15 min of relaxant and anesthetic administration. 1 7 These results are at variance with the findings of Lowry et al who showed a more marked effect of sevoflurane on rocuronium block during spontaneous recovery even after shorter periods of volatile agent administration.…”
Section: Discussionmentioning
confidence: 98%
“…[14][15][16] This may be the reason why in a recent study there was no marked prolongation in average reversal time of rapacuronium during sevoflurane compared to propofol anesthesia as the reversal was carried out within only about 15 min of relaxant and anesthetic administration. 1 7 These results are at variance with the findings of Lowry et al who showed a more marked effect of sevoflurane on rocuronium block during spontaneous recovery even after shorter periods of volatile agent administration.…”
Section: Discussionmentioning
confidence: 98%
“…Some demand a 30 to 40 min equilibration period of the muscular compartment when using inhaled anesthetics with a high blood-gas solubility, particularly for determination of infusion rates of neuromuscular blocking drugs. 13 Xenon has the lowest blood-gas solubility of all inhaled anesthetics by a wide margin. The solubility of volatile anesthetics in muscle is influenced by body temperature and the patient's age.…”
Section: Discussionmentioning
confidence: 99%
“…Quinze minutes après le début de la perfusion, sa vitesse était plus grande (P < 0,05) pour le groupe propofol (7,5 ± 4 and rocuronium. 5 However, prolongation of the duration of action of neuromuscular blocking agents is not always found, 6,7 and in certain settings the degree of potentiation is very modest. 8 In one study, isoflurane did not alter mivacurium infusion rates compared with propofol.…”
Section: Méthode : Chez 48 Patients Consentants Classifiés Asa I Ou mentioning
confidence: 99%
“…9 One possible explanation is that potentiation with volatile agents takes time to develop, because of the time taken for equilibrium of the agent with muscle tissue. 10 Sevoflurane has been reported to potentiate blockade produced by mivacurium, 11 rocuronium, 5,7 vecuronium, 12 and cisatracurium, 4 but the effect is not always consistent. For example, only a slight decrease was found for the ED 50 of mivacurium, and no change in its duration of action.…”
Section: Méthode : Chez 48 Patients Consentants Classifiés Asa I Ou mentioning
confidence: 99%